الدبلوماسية الجزائرية و بناء السلم في الساحل الافريقي ( مالي انموذجا ) - العايش, عواطف (جامعة الوادي university el-oued)
" تشكل منطقة الساحل الافريقي أحد المجالات الجيو- سياسية التي تثير اهتمام الفواعل الاقليمية و الدولية و مراكز البحوث و الدراسات في الوقت الحالي لكونها منطقة مهمة استراتيجيا و اقتصاديا و سياسيا و بيئيا....الخ . و من خلال التطور الذي شهدته المنطقة عبر الامتداد التاريخي ، فانها تعرضت للعديد من التهديدات نتيجة انعكاسات الاهمية الاستراتيجية للموقع الجغرافي بالاضافة الى تأثيرات النزاعات الاثنية و هشاشة الانظمة السياسية و كذا الشبكة العنكبوتية للتحديات الامنية ، و هذا ما فرض التأسيس الى مبدأ أفرقة الحلول لهاته التهديدات خاصة منطقة الساحل الافريقي و جنوب الصحراء . و قد تمكنت الجزائر من فرض منطقها الدبلوماسي بقوة على النطاق الاقليمي و العالمي على حد سواء نتيجة التعقد التشابكي للتهديدات الامنية بالمنطقة من خلال سعيها الدؤوب لتوفير الامن و السلم و تعزيز الاستقرار و بخاصة في ظل التحولات الاستراتيجية – الهيكلية الراهنة ، و السعي لتجسيد الطرح التوازني بين المصالح الامنية المشتركة بمنطقة الساحل الافريقي . ""The African Sahel region constitutes one of the geo-political areas that arouse the interest of regional and international actors and research and studies centers at the present time because it is an important strategically, economically, politically and environmentally....etc . Through the development that the region witnessed through the historical expansion, it has been exposed to many threats as a result of the repercussions of the strategic importance of the geographical location in addition to the effects of ethnic conflicts and the fragility of political systems, as well as the Internet of security challenges, and this is what imposed the establishment of the principle of solutions teams for these threats, especially The African Sahel and Southern Sahara . Algeria has been able to forcefully impose its diplomatic logic on the regional and global levels alike as a result of the intertwined complexity of the security threats in the region through its tireless pursuit to provide security and peace and enhance stability, especially in light of the current strategic-structural transformations, and seeking to embody the equilibrium between Common security interests in the African Sahel . "
م.س.ع.21
Keywords: الدبلوماسية ، الدبلوماسية الجزائرية ، بناء السلم ، الساحل الافريقي ، أزمة مالي .; Diplomacy, Algerian diplomacy, peace building, the African coast, the Mali crisis.